The Evaluation of Some Dietary Fiber Rich by-Products in Ice Creams Made from the Traditional Pudding - Kesme Muhallebi - SIÇRAMAZ, Hatice; AYAR, Ahmet; AYAR, Eda Nur (Journal of Food Technology Research, 2017)
The objective of this study was to investigate the effects of dietary fiber (DF)-rich by-products in Turkish traditional pudding kesme muhallebi and ice cream made from it. For this purpose, corn pulp, black carrot and apricot pomace were added in dessert samples. Dessert and ice cream samples were analyzed for their sensory attributes and textural properties. Black carrot pomace added samples had the lowest sensory attributes, while corn pulp added samples had comparable results with control samples. The obtained results in this study showed that the sensory properties of the desserts weren’t affected adversely with the addition of DF materials except for black carrot. Some of the food industry wastes can be available processing aids in functional food production. In addition, kesme muhallebi dessert was successfully introduced into ice cream, with higher sensorial attributes.